Medical vocation: need for its scientific study - Perales, Alberto (2013)
Objectives: To delimit medical vocation as a research issue and to propose a hypothesis for its scientific study. Methods: Review of pertinent international and national bibliography to elaborate the research questions. Results: The medical literature reviewed shows insufficient problem delimitation and poor presence of scientific method for its study as well as abundance of thoughtful reflections of paradigmatic physicians about its essence. Conclusions: Upon current dehumanization risk of medical practice and Health Care Systems to surrender to the professional market economic pressure, it is urgent to produce valid knowledge on the issue of medical vocation to allow Schools of Medicine to apply it in candidate’s selection exams as well as during the professional academic process.